Complications and mortality in hereditary hemorrhagic telangiectasia: a population-based study - Donaldson, J.W.; McKeever, Tricia M.; Hall, Ian P.; Hubbard, R.B.; Fogarty, Andrew W. (American Academy of Neurology, 2015)
OBJECTIVES: